Assessment of Autonomic Function in Moderate Aortic Stenosis - Connolly, Niall Patrick (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2026)
Introduction - The aortic valve is one of the four valves in the heart. All blood pumped to the body flows through the aortic valve as it exits the heart. It plays a vital role in preventing blood from flowing backwards into the heart and helping maintain steady blood flow and blood pressure to the body between heart beats. Aortic stenosis is a common condition where the aortic valve becomes narrowed and stiff, particularly in older adults. As the valve narrows, it becomes harder for the heart to push blood flow through it. Over time, this can lead to serious health problems and even death. Worryingly, an increased risk of death is seen not only when the valve is severely narrowed but also in moderate cases. Currently, the only treatment available is valve replacement, which is typically only offered when the disease becomes severe and symptoms develop, or in the presence of other markers of a poorer prognosis. Normally, our heart rate increases briefly after standing up and then decreases again after our body adapts to the new position. This process is controlled by the autonomic nervous system the body’s automatic control system for functions like heart rate and blood pressure. Poor autonomic function has also been linked to worse outcomes in various health conditions but its role in aortic stenosis hasn’t been well-studied. This study explored whether impaired autonomic function plays an important role in aortic stenosis by using a simple test that measures how quickly heart rate falls between 10 and 20 seconds after standing up, known as HRR10-20. A greater fall in heart rate (more negative HRR10-20) suggests better autonomic function and has been previously associated with better outcomes. We studied over 250 people, including those with moderate or severe aortic stenosis, as well as healthy adults of similar age. Our findings show that HRR10-20 is much slower in patients with more severe narrowing of the aortic valve. People with moderate narrowing had normal HRR10-20 but already showed early signs of nervous system stress including higher resting and peak heart rates and changes in heart rhythm patterns. These changes might reflect the body’s early attempts to compensate for the narrowing of the heart valve, even before damage occurs. Importantly the HRR10-20 did not improve after valve replacement, which raises concerns that some of the nervous damage may be long-lasting or irreversible if not caught early. This test could be a useful tool to help identify people with aortic stenosis who are at greater risk, even before they have severe disease or major symptoms appear. It is quick, non-invasive and easy to perform making it especially helpful in older or frail patients. The findings also support the idea that earlier treatment might be necessary to prevent lasting damage, but we cannot make a definitive link based on this data. The study is small in nature so the findings would need to be reproduced and expanded in a bigger study.
APPROVED
Keywords: Aortic Stenosis; Autonomic Dysfunction; Heart Rate Recovery